Dampak WISMP (Water Resources and Irrigation Sector Management Program) Terhadap Ketahanan Pangan Di Gunungkidul - Fahmi, Kurniawan; Utami, Angki Intan (Fakultas Pertanian, Universitas Ekasakti, 2025)
This study aims to analyze the impact of the Water Resources and Irrigation Sector Management Program (WISMP) on food security in Gunungkidul Regency by focusing on three variables: productivity, institutional empowerment, and farmer welfare. The study was conducted in three Kapanewon (sub-districts): Karangmojo (P3A Sri Mulyo), Nglipar (P3A Ngudi Rejeki), and Wonosari (P3A Marsudi Tani), with 67 farmer members who participated in the WISMP program as respondents. The results of the analysis indicate that all three independent variables have a positive effect on food security, with the most dominant influence coming from productivity and institutional empowerment. Farmer welfare also makes a positive contribution, although not significant. These findings indicate that the implementation of the WISMP program significantly contributes to improving local food security through improving aspects of production, institutions, and farmer welfare.